(untitled) (Research, Society and Development, 2020)
The objective of this study was to analyze the biopsychosocial repercussions, trace and characterize the sociodemographic profile, discuss the biological, psychological and social changes of patients with chronic renal failure on hemodialysis. This is a descriptive study with a qualitative approach. The sample consisted of twenty patients of both sexes, aged 27 to 71 years, who attend the hemodialysis sector of the Renal Therapy Center, located in Teresina-PI. In this research it was possible to verify, through the patients’ reports, that the referred treatment caused them physical limitations related to the debilitation and the lack of vigor to perform daily activities.Furthermore, the most reported social repercussion was the decrease in quality of life due to physical limitations. The most recurrent psychological repercussions in the reports were: experiences in the face of chronic kidney disease, a situation that is enhanced by feelings of fear, insecurity about the future, uncertainties about the evolution and limitations imposed by the disease. Support from family members and health professionals is essential for the patient to adapt to the changes arising from the experience of falling ill. Espiritualidade no tratamento hemodialítico o que mais relatam é a tentativa de manter uma estratégia de boa convivência com a máquina mesmo com as dificuldades, buscam a conformidade, e o refúgio é na fé, no apoio dos familiares e dos profissionais. The results evidenced, in the meantime, aim to contribute to the development of strategies for the prevention and treatment of chronic kidney disease, offering support not only physical, but also psychological, social and spiritual.